On the PAN-India Assessment of Elephant Corridors: Challenges, Opportunities, and Future Directions - Pandey, Ramesh K.; Natarajan, Lakshminarayanan; Mittal, Dheeraj; Udhayaraj, A.D.; Selvin, Muthamizh K.; Gupta, Dharmendra K.; Kumar, Rajendra; Tiwari, Virendra R.; Yadav, Satyaprakash; Habib, Bilal; Nigam, Parag (Indian Forester, 2024)
In the face of human expansion, which makes inroads into wildlife habitats, causing fragmentation and concomitant population isolation, wildlife corridors are recognized as an important tool to connect otherwise discrete corridors and populations. The wildlife corridors are particularly critical for species with high mobility and large range needs, such as the Asian elephants (Elephas maximus) whose range suffers unprecedented habitat fragmentation throughout Asia. In India, which harbors the largest extant wild population of Asian elephants, corridors remain a mainstay of connecting landscapes. Thus, securing elephant corridors is one of the main conservation strategies in the country. Adding to the previous pan-India assessments on elephant corridors, Project Elephant carried out a rapid assessment of elephant corridors identified by the respective states across India. The assessment culminated in an all-India report on elephant corridors, which identified 150 corridors across the four major elephant bearing regions in India. Here, the process involved in carrying out the countrywide assessment of elephant corridors is elucidated. Further, the major challenges facing elephant corridor identification and management have been elaborated. Approaches to effectively identify and conserve elephant corridors were articulated based on the learning acquired during the pan-India assessment.